2011
DOI: 10.3844/ajebasp.2011.47.57
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Perceived Quality, Perceived Value and Perceived Risk Towards Purchase Decision on Automobile

Abstract: Problem statement:As the level of competition keep on increasing in Malaysia automobile market, it is essential for every automobile producer companies to understand customer insight in order to further increase their share of wallet. Thus, they need to understand what factors might influence their customers' decision in purchasing an automobile. Therefore, the objectives of this research is to study the relationships of perceived quality, perceived value and perceived risk that will affect on Malaysia consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 41 publications
1
16
0
4
Order By: Relevance
“…Ye Xiaojing (Yee and Ng, 2011) is defined the chain stores have ten or more stores. Use the same trade names, trademarks, corporate identity system and controlled by the same regional head office or authorized agent.…”
Section: Fig 1: Chain Typesmentioning
confidence: 99%
“…Ye Xiaojing (Yee and Ng, 2011) is defined the chain stores have ten or more stores. Use the same trade names, trademarks, corporate identity system and controlled by the same regional head office or authorized agent.…”
Section: Fig 1: Chain Typesmentioning
confidence: 99%
“…Example of this application can be seen from Yee and San (2011). Yee and San (2011) emphasis that in business, consumer's prior knowledge on the product should not be neglected as this knowledge can lead to the purchase decision.…”
Section: Introductionmentioning
confidence: 99%
“…Yee and San (2011) emphasis that in business, consumer's prior knowledge on the product should not be neglected as this knowledge can lead to the purchase decision. Focusing on automobile business, Yee and San (2011) found that consumer buying decision may influenced by the quality, value and risk that they perceived.…”
Section: Introductionmentioning
confidence: 99%
“…In service industry, Simose and Dibb (2001) also stated powerful brands will raise consumers' faith for unseen value, give customers better product image or appreciate the intangible assets and decrease consumers' perceived financial, social, or safety risk. Yee and San (2011) claimed the perceived risk is the phenomenon when purchasing commercial goods in early stages by consumer's subjective evaluation. In the other words, customer tends to avoid the risky decision or the product or service they are not familiar with.…”
Section: Brand Equitymentioning
confidence: 99%
“…Sudhahar et al (2006) stated perceived risk of customer will influence purchasing behaviors and purchasing policy from customers. Yee and San (2011) claimed customers sense different risks when purchasing goods or services. Customer's purchasing desire will decrease when customers perceive higher purchasing risk.…”
Section: Introductionmentioning
confidence: 99%